PENEGAKAN HUKUM TERHADAP PELAKU PENCURIAN TERNAK DI DESA WALI ATE KECAMATAN WEWEWA BARAT KABUPATEN SUMBA BARAT DAYA PROVINSI NUSA TENGGARA TIMUR - Mateus Dairo, Ole (Kerta Dyatmika, 2026)
Livestock theft is an unlawful act (PMH) and is regulated in Article 363 paragraph (1) of the Criminal Code. Livestock theft is a criminal act of theft with aggravation in the form of principal (Article 362). The purpose of this study is to find out in depth the data and legal data sources related to the law enforcement process against perpetrators of livestock theft in the Wali Ate Village community and regarding the obstacles and efforts to enforce the law against livestock theft so that the fulfillment of the rights of residents of the Southwest Sumba correctional facility who are harmed can be achieved. The factors causing the occurrence of criminal acts of livestock theft include economic factors, environment, socialization, education and opportunity. The more widespread the occurrence of criminal acts of livestock theft, the more it will disrupt public order and tranquility and harm the victims. This study is classified as an empirical legal research type (quantitative). All data collected comes from primary data and secondary data. Relevant legal theories include the theory of law enforcement, the theory of legal certainty and the theory of legal justice. Based on the study and analysis of these theories, critical, logical and systematic discussion results can be obtained. The conclusion is that law enforcement against perpetrators of livestock theft in Wali Ate Village is carried out by the police sector of the West Wewewa Police Resort, namely by taking preventive and repressive actions through law enforcement and the involvement of the local government and the community in eradicating perpetrators of livestock theft in Wali Ate Village, West Wewewa District, Southwest Sumba Regency, East Nusa Tenggara Province.